Feeding preferences of oil palm pest subterranean termite Coptotermes curvignathus (Isoptera: Rhinotermitidae) - Yii, Jing Ee; Bong, Joseph Choon Fah; Hung, Patricia King Jie; Kadir, Jugah (Academic Journals, 2016)
Present study was conducted to investigate the feeding preferences of the pestiferous termite species in oil palm plantation, Coptotermes curvignathus and to develop an effective combination of toxicants and phagostimulant with concepts of a cost-effective and environmental friendly termite baiting technology. In choice feeding bioassays, size of bait and nutrient were investigated and found to significantly influence termite feeding preference. The results showed rubber wood sawdust was consumed 4-6 times more than rubber wood in granular and block form by C. curvignathus. It signified that sawdust was palatable and in easier consumable form than solid wood block and granules, which needed to be chewed by termite workers. Whereas for the nutrient preference test, glucose was most preferred by termites with the greater consumption of paper discs compared to other carbon and nitrogen sources. Formulated bait with combinations of 0.001 mg a.i L–1 fipronil, 108 conidia g–1 bait Metarhizium anisopliae and 1% glucose gave the greatest synergistic effect (χ2 = 17.889), followed by 108 conidia g–1 bait with glucose. The results demonstrated that glucose might be a key additive in development of an effective bait system for subterranean termite management.